The prevalence of gastric neoplasia is increased in patients with chronic liver disease compared to a healthy screening population - João Pedro Leal Moreira (2023)
Introduction: Gastric cancer (GC) is a major worldwide health concern. For several years now, numerous studies reported a higher prevalence of GC in patients with advanced chronic liver disease (ACLD). More recently the Baveno VII criteria were proposed to identify patients could safely avoid screening EGD. Therefore, our main objective was to evaluate the prevalence of gastric neoplasia in cACLD patients that underwent EGD for screening of gastro-esophageal varices. Material and Methods: The study analyzed 1845 patients, consisting of 481 cases and 1364 controls. The cases were asymptomatic cACLD patients, and the controls were asymptomatic healthy individuals. Histopathological findings of gastric neoplasia were classified according to the Lauren classification. We utilized SPSS v.27.0 for data analysis and different statistical tests such as t-test/one-way Anova, Mann-Whitney, and Kruskal-Wallis test to test hypotheses. Fisher's exact test or Pearson chi-square test were used to assess statistical differences between cases and controls. Binary logistic regression was used to identify factors associated with gastric neoplasia, and the significance level was set at p<0.05. Results: We found a higher prevalence of gastric neoplasia in patients with cACLD (4.2%) compared to the healthy population (1.1%). The prevalence of gastric carcinoma and dysplasia was 1.4% and 0.7%, respectively, and was significantly higher in cases than in controls. Age ≥60 years, absence of H. pylori infection, and OLGIM stage ≥ III were identified as risk factors for gastric neoplasia. 7 cases of gastric neoplasia were diagnosed in patients who, according to the Baveno VII criteria, could avoid EGD for gastro-esophageal varices. Discussion/conclusion: The study examined the prevalence of gastric neoplasia in patients with cACLD and compared it with healthy screening population. We found a 4-times higher prevalence of gastric neoplasia in patients with cACLD, with a higher prevalence of both gastric dysplasia and carcinoma higher in cases than controls. The study highlights the possible role of endoscopic screening as an opportunistic method for an early diagnosis of gastric neoplasia in patients with cACLD. We recommend the use of endoscopic submucosal dissection (ESD) and surgical treatment as possible approaches to treat gastric carcinoma in patients with cACLD, with ESD associated to better outcomes. This corresponds to the largest study that demonstrated an increased prevalence of GC in cACLD population and it is the first one to suggest that endoscopic screening for varices in cACLD patients can lead to early detection of gastric cancer and better outcomes with early intervention.